STRATEGI PEMIKIRAN POLITIK KE ARAH PENEGASAN DAN PENGUATAN SISTEM PEMERINTAHAN PRESIDENSIIL DI INDONESIA (KAJIAN DARI PERSPEKTIF HUKUM TATA NEGARA DAN HAK ASASI MANUSIA) - Budiana, I Nyoman; Warta, I Made (Jurnal Legislasi Indonesia, 2019)
Indonesia adheres to a representative democratic system that prioritizes the interests of citizens in decisions made by the government. In this study we will discuss the strategies of people's political thinking in the framework of affirmation and strengthening the presidential system in Indonesia. Data collection and analysis in this study uses a normative juridical approach by collecting legal material from various libraries, both in the form of principles, concepts and legal theories that are in accordance with the issues of constitutional law that are adopted. The analysis was conducted in a normative juridical reseach and the presentation of legal analysis was described descriptively qualitatively.Constitutionally, the presidential system is characterized by an equal position between parliament and the executive. The Indonesian constitutional system is in the transition phase of democracy which implements a presidential based multi-party democracy system. With the simplification of the party in elections, it can guarantee stability in executive and parliamentary relations in the administration of the State. The implementation of the electoral system with sound balance cannot form a formidable parliament quality. Political thinking in the framework of affirming and strengthening presidential systems in constitutional practice is part of the people's political rights guaranteed by human rights.